Dribble Training Model For Junior Athletes Basketball Sports - Fahmi, Fadlilah; Ariestika, Elsa; Febriyanto, Andita (Jurnal Pendidikan Jasmani (JPJ), 2025)
The purpose of this research and development is to produce a basketball dribble training model for junior athletes and to determine the effectiveness, efficiency and attractiveness of athletes to the model. This study uses the Borg and Gall Research & Development (R & D) development research method. The subjects of this study were club athletes consisting of 60 athletes. The instruments of this research and development were questionnaires, questionnaires, and basketball dribble test instruments, the stages of this research and development are: needs analysis; expert evaluation; limited trials; and main trials. The effectiveness test of the model used a dribble test to determine the ability of junior athletes to dribble basketball before and after the treatment of the developed dribble model, the initial test obtained an athlete's dribble time of 11.86 seconds, after being given treatment in the form of a dribble model, an increase in time was obtained faster by 8.77 seconds. So this basketball dribble model is effective in improving junior athletes' basketball dribble training. Based on the results of the development, it can be concluded that: The basketball dribbling training model for junior athletes can be developed and applied in club training. The basketball dribbling training model for junior athletes that has been developed has shown an increase as shown in the results of the pretest and posttest data testing, there is a significant difference between before and after the model treatment.